Inequality and the duration of growth - Jonathan D. Ostry (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
The relationship between income inequality and economic growth is complex. Some inequality is integral to the effective functioning of a market economy and the incentives needed for investment and growth. But inequality can also be destructive to growth, for example by amplifying the risk of crisis or making it difficult for the poor to invest in education. This paper finds that the duration of growth spells is robustly associated with more equality in the income distribution. Inequality matters, moreover, even when other determinants of growth duration – external shocks, initial income, institutional quality, openness to trade, and macroeconomic stability – are taken into account.
Keywords: O11; O15; O47; E62; H23; 330; inequality; redistribution; economic growth